Self Conception of Cocoa Farmer’s Children (Case Study : Cocoa Planting Centre In South Sulawesi) - Tuti Bahfiarti; Andi Alimuddin Unde; Muhammad Nadjib (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2017)
The self-concept of children of cocoa farmers is a frame of reference for him to interact with the external world. The self-concept is relatively consistent to the situation, timing, and behavior patterns are relatively consistent. Formation of child's self concept is affected by external factors and internal environment of the child interacting with other individuals.A qualitative approach which refers to the case study. The purpose of case studies to analyze specific issues. Location of the study in two sub centers cocoa plantations in South Sulawesi, namely: Luwu and Luwu Timur. Instruments of data collection using observation, interview, Focuss Group Discussion (FGD).Results of the study revealed that self-concept of children of cocoa farmers develop positive self-concept. Characteristics of positive self-concept is a child have pride as children of cocoa farmers and have self-confidence and motivation high. For example, the motivation to aspire to be a successful cocoa farmer, proud as children of cocoa farmers, contribute actively to help their parents, independent, polite, responsible, patient behaves in the face of failure, and be able to resolve problems in the environment.The self-concept of children of cocoa farmers tend to be negative, for example, less accepting and shy as children of cocoa farmers, lack the motivation to become cocoa farmers. On the other side of this category of children lacking the initiative to help their parents, and avoiding work as a cocoa farmer. Behavior that is less willing to take decisions, are less able to withstand the pressures and tend to avoid the difficult conditions in the environment. Keywords: Cocoa Farmer, Interpersonal Communication, Self Concept, South Sulawesi